Water Quality of Bakun Reservoir, Belaga, Sarawak - Theresa, Muan (Universiti Malaysia Sarawak (UNIMAS), 2013)
A study of the water quality changes of Bakun Reservoir was conducted on 4-7 December 2012 and 9-12 April 2013. Six stations were selected at three different depths, representing the open water body of the reservoir. A total 14 water quality parameters were measured and (DOE-WQI) was calculated and classified as INWQS. The physicochemical parameters were temperature, DO, conductivity, pH, turbidity and transparency which were conducted in-situ; TSS, BOD5, COD, and nutrient analysis such as ammonia-nitrogen, nitrate, nitrite and orthophosphate were conducted as ex-situ. The biological parameter, chlorophyll-a analysis was also carried out. The temperature at subsurface is consistently higher for all stations, the DO is decreasing as depths increases and the pH is above 6 at the subsurface. The TSS and turbidity also increases with depths. Low DO value as the depths increases are also corresponded with high BOD5 level. Results show that Bakun Reservoir is classified as Class III.